Mrežne organizacije - novi vzorec 21. stoletja - Semolič, Brane (Strojniški vestnik, 2007)
Globalization and rapid technological advances require organizations to develop competitively at the world level. This poses great problems, particularly for small and medium-sized companies, which have limited resources in terms of personnel, money, development, production capacities andk nowledge. Therefore, it is very necessary for them to focus on selected areas of business activities where they are likely to develop competitiveness on the world market. Other products or services required to perform their current or anticipated business activities can be procured outside their own organization in the open market. Generally speaking, the technologically developed companies from developed countries in most cases try to find production partners with cheap manpower to perform their activities with lower added value. The organizations from technologically less-developed regions try to find the business partners for the development and transfer of new technologies into practice in their own companies. Of course, for the organizations from developed and less-developed countries and regions there can be several reasons why they try to find business partners outside their own organization. Here, we are concerned with the organizations wanting to develop by constantly innovating in all areas of their business activities. Organizations also face the need to redefine the way they set up their business activities. The concepts, offered by theory, issue from the theory of network organization, project management and industrial clusters.
Keywords: podjetja; organizacija dela; združevanje; povezovanje; sodelovanje; specializacija; projektno vodenje